Utilización de un prebiótico natural de aji de gallinazo capsicum frutescens en el engorde de pollos broilers - Morocho Chuba, Enrique Bladimir (2010)
In the Experimental Farm Facilities "Santa Inés" Technical University of Machala, Provincia del Oro, 5 m, is conducting an inquiry with the following objectives: 1 .- Check the productive parameters of broilers with the use of a natural prebiotic. 2 .- To determine the effect of the buzzard pepper (Capsicum frutescens) in the production of broiler chickens 3 .- To establish the profitability of production with the use of poultry manure chili (Capsicum frutescens). We worked with 450 broiler chickens in floor from birth to 42 days old baby chicks were distributed 18 homogeneous groups of 25 chickens each, six treatments were considered as the dosage of buzzard pepper (Capsicum frutescens) in water drinking (25gr/4lit, 50gr/4lit. 75gr/4lit. 100gr/4lit. 125gr/4lit.) with three replicates each. The experimental design was completely randomized and the mean separation test of Duncan, with a significance level 0.05. The feed was a commercial feed, the parameters that were investigated for each of the treatments were: weight gain, feed intake, feed conversion, mortality, cost of production, growth or total absence of flora, colimetria, fungi and yeasts by bacterial seeding. To which the chickens were weighed at baseline and weekly until the investigation ended, the outcome was reached the following conclusions: The average values for weight gain the highest increase corresponded to T1 3233.99 gr. While the smaller To increase was for the control group corresponded with 2898.05 g Food consumption was outstanding value for the T5 5252.67 gr. And corresponded to lower power in 4761.33 To gr. The highest consumption of pepper was hit by the T5 with 12781.14 gr. and does not show the To and consumption is not given any amount of pepper 7. The best feed conversion was obtained in T1 1.56% The relevance was obtained in T1 with $ 60.95 cents and the lowest value was for the To $ 53.13 cents. In the highest percentage mortality as the control group was 8% and the group was no mortality tube for T3.